2014
DOI: 10.25100/cm.v45i4.1690
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la altura del arco del pie en la calidad de vida, de escolares de entre 6 a 12 años

Abstract: Objective: To determine whether arch height has an effect on the health-related quality of life of schoolchildren. Methods: One hundred and thirteen schoolchildren attended an out-patient centre where self-reported data were recorded, their feet were classified into one of three groups according to their arch index (high, normal or low) and the scores obtained from the Foot Health Status Questionnaire (FHSQ - Spanish version) were compared. Results: The groups with high, low and normal arch recorded lower s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
3
13
0
1
Order By: Relevance
“…These studies have demonstrated that hallux valgus, calcaneal apophysitis, foot arch height, heel pain, chronic ankle instability and onychomycosis negatively affect foot function and foot health. 23–27 …”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that hallux valgus, calcaneal apophysitis, foot arch height, heel pain, chronic ankle instability and onychomycosis negatively affect foot function and foot health. 23–27 …”
Section: Discussionmentioning
confidence: 99%
“…The difference in arch type is a contributory factor in sports injuries, which could affect and influence physical performance [3,8]. Furthermore, poor exercise behaviors might also lead to progressive deformation in arch morphology, resulting in foot problems and affecting the quality of life [1,[9][10][11]. López-López et al [11] indicated that patients with foot problems present a negative impact on the quality of life related to podiatry and foot health, especially in women.…”
Section: Introductionmentioning
confidence: 99%
“…Foot morphological indexes represented by arch height have also been reported to affect health-related quality of life [10,12]. In the past two decades, arch height index (AHI) has been recognized as a valid and reliable indicator for evaluating arch structure [3,4,8,12], which was outlined by Williams and Mcclay in 2000 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Foot skin is a first barrier in the human body, and its function is related with mechanisms of protection, thermoregulation and sensitivity . Although previous researches have been undertaken to assess the impact of the QoL related to foot health in patients with hallux valgus, children with foot arch, population with flat foot, menopausal women, sea workers and pregnant women, no study has previously focused on the relationships with MHL.…”
Section: Discussionmentioning
confidence: 99%